Clinical Efficacy of Piper betle L. Nanoemulgel as an Adjunct to Scaling and Root Planing in Chronic Periodontitis: A Randomized, Double-Blind, Placebo-Controlled Trial - Muhammad Ashraf; Eduardo Michael Perez (Eureka Herba Indonesia, 2025)
This study evaluated the clinical efficacy of a Piper betle L. (betel leaf) nanoemulgel as an adjunct to scaling and root planing (SRP) in chronic periodontitis through a randomized, double-blind, placebo-controlled trial. Sixty-four patients with Stage III Grade B periodontitis were randomized to P. betle nanoemulgel (5% w/w ethanolic extract standardized to ≥30 mg/g hydroxychavicol; n = 32) or placebo gel (n = 32), applied subgingivally at baseline, week 2, and week 4 as adjuncts to SRP, at a private hospital in Palembang, Indonesia. The nanoemulgel had a mean droplet size of 78.4 ± 12.6 nm, polydispersity index 0.218, zeta potential −32.6 mV, and encapsulation efficiency 87.3%. Primary outcomes were probing pocket depth (PPD), clinical attachment level (CAL), bleeding on probing (BOP), and gingival index (GI) at 12 weeks. The intervention group showed significantly greater PPD reduction (−2.58 ± 0.68 vs −1.56 ± 0.74 mm; p < 0.001; Cohen d = 1.43), CAL gain (d = 1.23), BOP reduction (d = 1.12), and GI improvement (d = 1.25). Gingival crevicular fluid TNF-α decreased to 18.4 ± 8.2 versus 28.6 ± 10.4 pg/mL (p < 0.001; d = 1.09). Adverse events were limited to mild transient burning in 12.5% of patients. Piper betle nanoemulgel provided significant adjunctive clinical benefit in chronic periodontitis through anti-inflammatory and antimicrobial mechanisms, supporting its integration into evidence-based herbal periodontal therapy.